Capnocytophaga ochracea infection: two cases and a review of the published work. Issue 9 (September 1984) - Hawkey, P M; Malnick, H; Glover, S A; Cook, N; Watts, J A
Abstract : Bacteria of the genus Capnocytophaga are recently recognised pathogens which may cause oral disease and subsequent septicaemia in the immunocompromised host. We present two cases of infection caused by Capnocytophaga ochracea; a soft tissue infection in an immunologically normal patient and an episode of septicaemia in a child with leukaemia. The microbiology, pathogenicity, and antimicrobial susceptibility of the genus capnocytophaga are reviewed.